Stabilization Of Thickened-Activated Sludge Through The Anoxic-Aerobic Digestion Process - Tan, Ming Ying (2002)
Aerobic digestion is widely used to treat waste-activated sludge and thickened sludge from wastewater treatment plant due to its shorter retention time and achieving the same efficiency in solids volume reduction compared to anaerobic digestion. However, the supernatant and filtrate from the aerobic digestion system contain high concentration of suspended solids. The nitrogen which had been embedded in sludge is solubilized to form ammonical and nitric nitrogen which in tum transferred to the liquor and cause the increase of nitrogen loading in sewage treatment plant. In this study, anoxic-aerobic digestion is applied to remove both the mixed-liquor volatile suspended solids (ML VSS) and soluble nitrogen simultaneously. The objectives of the study are to investigate and evaluate the removal efficiency of both ML VSS and soluble nitrogen by anoxic-aerobic digestion and compared to the aerobic control digesters, with and without lime control. By applying anoxic-aerobic digestion, a comparable of ML VSS reduction was gained to aerobic digestion. 66.12% and 63.00% of MLVSS destruction was found in both anoxic-aerobic digesters, with and without methanol addition respectively.